Condition-dependent sexual reproduction is driven by benefits, not costs of sex. (23rd September 2021) - Lever, Jessica; Drapes, Sally; Hall, Matthew D; Booksmythe, Isobel
Abstract: Facultative sexual organisms must allocate resources to both asexual and sexual reproduction. Optimal patterns of investment in sex depend on the relative costs and benefits of each reproductive mode, and may consequently be context- and condition-dependent. Two proposed explanations for the observed variation in investment in sex among facultative sexual lineages invoke alternative condition-dependent scenarios. Under the fitness-associated sex hypothesis, sex is predicted when individuals are in poor condition or experience stressful environments. Under the resource-demanding sex hypothesis, sex is only affordable to individuals in good condition experiencing favourable environments. Direct tests of these contrasting hypotheses are rare; moreover, investment in different components of sexual reproduction responds differently to cues promoting sex, and may be subject to different energetic constraints. Using genotypes of facultative sexual Daphnia carinata that differ in their level of investment in sex, we manipulated resource availability while accounting for day length (a seasonal cue for sex) to evaluate these hypotheses. The sexual response to day length depended on resource availability: increased day lengths and reduced food availability increased the production of sexual eggs, and relative investment in males, in a manner consistent with the fitness-associated sex hypothesis. The pattern of condition-dependence was specific to each component of reproductive investment – while male production covaried with asexual fecundity across genotypes, increased sexual egg production was associated with reduced asexual reproduction. Our results suggest that investment in sex is determined largely by its context-dependent advantages, and that this investment is not moderated by immediate costs to asexual reproduction. Abstract : For animals that reproduce both sexually and asexually, context matters in determining which form of reproduction to use. Australian waterfleas increase their use of sex in summer (when temperature effects can lead to population collapse) to varying extents. We find that, contrary to a hypothesis suggesting energetic demands of sex require animals to be well-fed, waterfleas use sex more under the stress of starvation, even when it costs them by reducing their asexual reproduction.